Innovation Strengthens the Influence of Digitalization and Entrepreneurial Orientation on Business Performance - Ratnawati, Kusuma; Susilowati, Christin; Yuana, Pusvita; Dewantara, Prasetya Putra; Nazzal, Ayman (Jurnal Aplikasi Manajemen, 2024)
MSMEs are embedded with dynamic and innovative new ideas, identifying opportunities that the big business world may not be aware of, offering jobs, creating wealth, increasing economic growth, and generating additional capital. The main objective of this study is to examine how innovation mediates the effects of digitalization and entrepreneurial orientation on company performance among MSME businesses in East Java, Indonesia. This study was quantitative research conducted on MSME business actors across East Java. Four hundred respondents were spread randomly. Research data was collected using a questionnaire, and the results were analyzed using PLS software. The results of this study indicate that digitalization and entrepreneurial orientation have a significant positive effect on innovation and the performance of MSMEs. This study also found a significant positive direct effect of innovation on performance. This study also examines the indirect effect which shows that innovation plays a mediating role in the influence of digitalization and entrepreneurial orientation on performance. MSMEs' digital awareness, knowledge, skills, and capabilities were learned and applied quickly due to the demands of adapting to the COVID-19 pandemic, which occurred sometime before this study was conducted. Thus, MSMEs have implemented digitalization sufficiently, which unknowingly, in the long term, has had a positive impact on increasing innovation and performance. On the other hand, this is not only related to digital capacity; MSMEs use networking talents, learning capacity, marketing skills, creativity, and risk-taking capacity as forms of entrepreneurial orientation, directly driving increased MSME performance financially and non-financially.